Regulation of Nigeran Accumulation by Aspergillus aculeatus - Gold, Michael H. (1973)
Nigeran (mycodextran), an unbranched glucan consisting of alternating α,1–4 and α,1–3 linkages, is accumulated intracellularly by Aspergillus aculeatus, under conditions of nitrogen limitation and low pH (optimum pH 5.0). Both conditions are necessary. Nigeran is synthesized de novo from exogenous glucose and accounts for about 20% of the glucose transported by the mycelium. The polymer is diluted out but not degraded when the mycelium is transferred to fresh medium containing NH(4)(+). Cycloheximide prevents development of the nigeran biosynthetic system. The addition of substrate levels of NH(4)(+) to nigeran-accumulating mycelium immediately suppresses further nigeran buildup, presumably by diverting glucose to the biosynthesis of amino acids, nucleotides, etc.